Assessment in VLE Supported Foreign Language Learning - Kalamarz, Ryszard (International Journal of Research in E-learning, 2015)
The paper focuses on the role of Virtual Learning Environments in the scope of different types of assessment in foreign language learning and teaching promoting learner autonomy and developing such key competences as learning to learn. Effective language education calls for a more learner-oriented approach to assessment and Learning Management Systems such as Moodle seem to respond to such needs in the computer assisted teaching/learning process.